Macro-Fiscal Gains from Anti-Corruption Reforms in the Republic of Congo - Melina, Giovanni (IMF Working Papers; Working Paper ;, 2019)
This paper argues that oil revenue management and public investment in Congo are vulnerable to corruption as a result of limited transparency and accountability. Corruption has potentially contributed to poor macro-fiscal outcomes. The paper acknowledges the authorities' anti-corruption efforts made so far and proposes further critical reforms to reduce remaining vulnerabilities. Using a dynamic stochastic general equilibrium model results show that, depending on the reforms adopted, the potential additional growth can range between 0.8 to 1.8 percent per year over the next 10 years, and debt can decline by 2.25 to 3 percent of GDP per year over the same period. These results suggest that macrofiscal gains from anti-corruption reforms could be substantial even under conservative reform scenarios.